Demonstration of Improved Charge Transfer in Graphene/Au Nanorods Plasmonic Hybrids Stabilized by Benzyl Thiol Linkers. (7th February 2016) - Bianco, Giuseppe Valerio; Giangregorio, Maria Michela; Losurdo, Maria; Sacchetti, Alberto; Capezzuto, Pio; Bruno, Giovanni
Abstract : Hybrids based on graphene decorated with plasmonic gold (Au) nanostructures are being investigated as possible materials combination to add to graphene functionalities of tunable plasmon resonance and enhanced absorption at selected wavelength in the visible-near-infrared region of the spectrum. Here, we report a solution drop-casting approach for fabricating stable hybrids based on chemical vapor deposition (CVD) graphene and Au nanorods, which are able to activate effective charge transfer from graphene. We demonstrate that CVD graphene functionalization by benzyl thiol (BZT) provides the linker to strong anchoring, via S-Au bonds, Au nanorods to graphene. Optical measurements by spectroscopic ellipsometry give evidence of the introduction of plasmon resonances at 1.85 and 2.25 eV in the Au nanorods/BZT/graphene hybrids, which enable surface enhanced Raman scattering (SERS) detection. Furthermore, an effective electron transfer from graphene to Au nanorods, resulting in an enhancement of p-type doping of graphene with a consequent decrease of its sheet resistance, is probed by Raman spectroscopy and corroborated by electrical measurements.